2015
DOI: 10.2337/dc14-2311
|View full text |Cite
|
Sign up to set email alerts
|

Normative Values for Corneal Nerve Morphology Assessed Using Corneal Confocal Microscopy: A Multinational Normative Data Set

Abstract: OBJECTIVECorneal confocal microscopy is a novel diagnostic technique for the detection of nerve damage and repair in a range of peripheral neuropathies, in particular diabetic neuropathy. Normative reference values are required to enable clinical translation and wider use of this technique. We have therefore undertaken a multicenter collaboration to provide worldwide age-adjusted normative values of corneal nerve fiber parameters.RESEARCH DESIGN AND METHODSA total of 1,965 corneal nerve images from 343 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
168
3
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(192 citation statements)
references
References 36 publications
17
168
3
4
Order By: Relevance
“…The results of the current study also revealed a small increase in CNFTo in histology images. Even though the observed difference in our study is in line with the recent report of age-dependent increase in tortuosity, 4 the small sample size examined in our study and the relatively small difference in mean age between the histology and IVCM groups, prevented us from drawing any meaningful conclusions on age-related changes in SBP tortuosity. Furthermore, no clear Figure 2 Local variability of the parameter CNFL.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The results of the current study also revealed a small increase in CNFTo in histology images. Even though the observed difference in our study is in line with the recent report of age-dependent increase in tortuosity, 4 the small sample size examined in our study and the relatively small difference in mean age between the histology and IVCM groups, prevented us from drawing any meaningful conclusions on age-related changes in SBP tortuosity. Furthermore, no clear Figure 2 Local variability of the parameter CNFL.…”
Section: Discussionsupporting
confidence: 57%
“…Alterations of SBP morphological parameters derived from IVCM images serve as potential biomarkers for early diagnosis of various neurodegenerative diseases. [1][2][3][4] However, the ability of IVCM to adequately resolve intimate details of SBP anatomy remains incompletely understood since the field of view of a conventional IVCM image is relatively small (400 × 400 μm 2 ) and might be insufficient for reliable assessment of SBP morphology. 5 Advancements in imaging extended areas of the corneal SBP by creating large-scale montages [6][7][8] have substantially alleviated this principal limitation of IVCM.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from ageand gender-specific normative values, the paper also standardizes the protocol used to derive such data. A similar endeavor with the CCM, published recently, has pooled 1,965 images form 343 healthy volunteers across Europe, Australia, and North America, allowing practical and singleprotocol-driven use of this technique [146].…”
Section: Validation Of Normative Valuesmentioning
confidence: 99%
“…Both the somatic and autonomic peripheral nervous system change with age [1,32,39,146]. It is therefore important that accurate normative data is determined with modern sensitive techniques developed for the detection of DSPN.…”
Section: Validation Of Normative Valuesmentioning
confidence: 99%
“…These fibres can be visualized and quantified by using in vivo corneal confocal microscopy, a noninvasive technique that rapidly evolved from a research technique to an emerging clinical tool 157 . Development of automated corneal nerve image analysis [158][159][160][161] and, most importantly, the establishment of reference values 162 have made corneal confocal microscopy a new and reliable diagnostic tool for SFN. The exact role of the technique in the diagnosis of individual patients with suspected SFN in clinical practice, however, remains to be determined, and requires further studies in future.…”
Section: Corneal Confocal Microscopymentioning
confidence: 99%